2023
DOI: 10.3389/fpls.2023.1162893
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome analysis reveals flavonoid changes during the leaf color transition in Populus × euramericana ‘Zhonghuahongye’

Abstract: IntroductionTo investigate the mechanism of leaf color change at different stages in Populus × euramericana ‘Zhonghuahongye’ (‘Zhonghong’ poplar).MethodsLeaf color phenotypes were determined and a metabolomic analysis was performed on leaves at three stages (R1, R2 and R3).ResultsThe a*, C* and chromatic light values of the leaves decreased by 108.91%, 52.08% and 113.34%, while the brightness L values and chromatic b* values gradually increased by 36.01% and 13.94%, respectively. In the differential metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…More than 100 compounds have been isolated from Populus nigra extract, including phenolic compounds, terpenoids, flavonoids, flavanone, caffeic and p-coumaric acids, and nearly 50 molecules from the essential oil of its buds ( Tebbi & Debbache-Benaida, 2022 ). To date, several studies have focused on the chemical composition of Populus red leaves ( Tian et al., 2021 ; Chen et al., 2023 ), whereas no further analysis has been conducted on the difference in the composition between red and green leaves throughout the lifecycle. In this study, we profiled the flavonoid compositions of the red and green leaves of Populus × euramericana ‘Zhonghuahongye’ at three stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 100 compounds have been isolated from Populus nigra extract, including phenolic compounds, terpenoids, flavonoids, flavanone, caffeic and p-coumaric acids, and nearly 50 molecules from the essential oil of its buds ( Tebbi & Debbache-Benaida, 2022 ). To date, several studies have focused on the chemical composition of Populus red leaves ( Tian et al., 2021 ; Chen et al., 2023 ), whereas no further analysis has been conducted on the difference in the composition between red and green leaves throughout the lifecycle. In this study, we profiled the flavonoid compositions of the red and green leaves of Populus × euramericana ‘Zhonghuahongye’ at three stages.…”
Section: Discussionmentioning
confidence: 99%
“…In Chen’s study, at three stages of leaf development (R1, R2, and R3) of Populus × euramericana ‘Zhonghuahongye’, 81 differentially abundant metabolites were detected in the R1 vs. R3 comparison, 45 were detected in the R1 vs. R2 comparison, and 75 were detected in the R2 vs. R3 comparison. Ten metabolites showed significant differences in all comparisons, which were mostly flavonoid metabolites ( Chen et al., 2023 ). Unlike previous reports, our study observed leaves from the tender stage to the mature stage of Populus × euramericana ‘Zhonghuahongye’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its further popularization and application are limited due to its single leaf color. In recent years, many kinds of coloredleaf poplars with splendid ornamental values, such as 'Zhonghong poplar' (ZHP) [3], 'Quanhong poplar' (QHP) [4], and 'Caihong poplar' (CHP) [5], have been bred from the bud sport of L2025. They are very suitable for urban, garden, and road beautification and bring great economic, social, and ecological benefits [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on leaf color changes in 'Zhonghuahongye' have primarily focused on leaf pigment changes and metabolite changes [10]. Although metabonomic studies for flavonoids have been conducted using 'Zhonghuahongye' [11], there has been limited research focusing on flavonoid biosynthesis. Additionally, the molecular mechanism of flavonoid accumulation and biosynthesis in 'Zhonghuahongye' remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%